Recombinant Saccharomyces cerevisiae strain triggers acetate production to fuel biosynthetic pathways - Ferreira, Bruno S. (2020)
Although the metabolism and physiology of the growth of yeast strains has been extensively studied, many questions remain unanswered when the induced production of a recombinant protein is concerned. This work addresses the production of a Fusarium solani pisi cutinase by a recombinant Saccharomyces cerevisiae strain induced through the use of a galactose promoter. It was observed that whenever the strain needed to activate biosynthetic pathways, either for cutinase synthesis, or for the synthesis of the enzymes required for galactose intake, acetate production occurred. The on-line detection of acetate in the medium might prove useful for the control and the supervision of recombinant protein production processes using yeast. The volumes of acid and base added to control the pH throughout the time course of the cultivations were used to calculate an on-line estimator for acetate concentration.